What internet digitalization brings to early childhood in family education in China? - Yu, Liya; Hamsan, Hanina Halimatusaadiah; Darshan Singh, Sarjit Singh; Cheng, Longyue (Human Resource Management Academic Research Society, 2024)
The Internet digital time has been arriving as a result of advances in social science and technology, impacting all facets of Chinese people’s life, including early childhood education and family education. The early childhood family education field has experienced significant growth in both scope and quality due to the widespread influence of the Internet. Additionally, family-school interaction has played a greater role in the early childhood education process. Real issues have, however, been progressively brought about by young children's lack of judgement and self-control in the digital age, their vulnerability to physical health issues, and their parents' lack of genuine communication with them. By examining the advantages and drawbacks of the digital Internet in the early childhood education, we propose strategies to create a healthy digital living environment, reasonably plan the time for children to use the Internet, and organically connect online and offline communication, so as to improve the effectiveness of early childhood family education and better promote the healthy growth of children.